Is perceived athlete leadership quality related to team effectiveness? A comparison of three professional sports teams - Fransen, K.; Haslam, S. A.; Mallett, C. J.; Steffens, N. K.; Peters, K.; Boen, F. (Journal of Science and Medicine in Sport, 2017)
Objectives: Researchers have argued that leadership is one of the most important determinants of team effectiveness. The present study examined the extent to which the perceived quality of athlete leadership was related to the effectiveness of elite sports teams. Design: Three professional football teams (N = 135) participated in our study during the preparation phase for the Australian 2016 season. Methods: Players and coaching staff were asked to assess players` leadership quality in four leadership roles (as task, motivational, social, and external leader) via an online survey. The leadership quality in each of these roles was then calculated in a social network analysis by averaging the indegree centralities of the three best leaders in that particular role. Participants also rated their team`s performance and its functioning on multiple indicators. Results: As hypothesized, the team with the highest-quality athlete leadership on each of the four leadership roles excelled in all indicators of team effectiveness. More specifically, athletes in this team had a stronger shared sense of the team`s purpose, they were more highly committed to realizing the team`s goals, and they had a greater confidence in their team`s abilities than athletes in the other teams. Moreover, this team demonstrated a higher task-involving and a lower ego-involving climate, and excelled on all measures of performance. Conclusions: High-quality athlete leadership is positively related to team effectiveness. Given the importance of high-quality athlete leadership, the study highlights the need for well-designed empirically-based leadership development programs.